Post-exercise Hypotension Following a Single Bout of High Intensity Interval Exercise vs. a Single Bout of Moderate Intensity Continuous Exercise in Adults With or Without Hypertension: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Marçal, Isabela Roque [UNESP]; Goessler, Karla Fabiana; Buys, Roselien; Casonatto, Juliano; Ciolac, Emmanuel Gomes [UNESP]; Cornelissen, Véronique A. (Frontiers, 2021)
Background: Post-exercise hypotension (PEH) is an important tool in the daily management of patients with hypertension. Varying the exercise parameters is likely to change the blood pressure (BP) response following a bout of exercise. In recent years, high-intensity interval exercise (HIIE) has gained significant popularity in exercise-based prevention and rehabilitation of clinical populations. Yet, to date, it is not known whether a single session of HIIE maximizes PEH more than a bout of moderate-intensity continuous exercise (MICE). Objective: To compare the effect of HIIE vs. MICE on PEH by means of a systematic review and meta-analysis. Methods: A systematic search in the electronic databases MEDLINE, Embase, and SPORTDiscus was conducted from the earliest date available until February 24, 2020. Randomized clinical trials comparing the transient effect of a single bout of HIIE to MICE on office and/or ambulatory BP in humans (≥18 years) were included. Data were pooled using random effects models with summary data reported as weighted means and 95% confidence interval (CIs). Results: Data from 14 trials were included, involving 18 comparisons between HIIE and MICE and 276 (193 males) participants. The immediate effects, measured as office BP at 30- and 60-min post-exercise, was similar for a bout of HIIE and MICE (p > 0.05 for systolic and diastolic BP). However, HIIE elicited a more pronounced BP reduction than MICE [(−5.3 mmHg (−7.3 to −3.3)/ −1.63 mmHg (−3.00 to −0.26)] during the subsequent hours of ambulatory daytime monitoring. No differences were observed for ambulatory nighttime BP (p > 0.05). Conclusion: HIIE promoted a larger PEH than MICE on ambulatory daytime BP. However, the number of studies was low, patients were mostly young to middle-aged individuals, and only a few studies included patients with hypertension. Therefore, there is a need for studies that involve older individuals with hypertension and use ambulatory BP monitoring to confirm HIIE's superiority as a safe BP lowering intervention in today's clinical practice. Systematic Review Registration: PROSPERO (registration number: CRD42020171640).
Keywords: ambulatory blood pressure; high intensity interval exercise; hypotension; moderate intensity aerobic exercise; office blood pressure; post-exercice; systematic review & meta-analysis